Road signage pattern using augmented reality / Ahmad Hasbullah Hashim - Hashim, Ahmad Hasbullah (2010)
People always ignore the signboard while driving on the road even knowing it is important to alert us. Without it, we are not notice that what kind of danger will comes in front of us. Therefore, many accidents occur, one of them is lost sight of signboard. All this happen because people like to steal the signboard due to the material. In addition, the cost production to replace the new one is quite expensive. The other issue is about the representation of what on the board is not clear. Driver does not know actually what written on the board about dangerous that come later on. The solution of this entire problem, it brings to the planning an application development on the phone based 3D modelling by using augmented reality. It seems to be like this; basically all people can alert the appearance of signage on the road situation but it is not very effective. It is because that technique of tracking is slow. This project proposes an adaptive tracking technique whereby tracking will be done on selected frames using optical flow analysis. The actual movement will be predicted on this analysis. After analysis, several testing is conducted to prove that the proposed method is better compared to existing way.